Optimization Formula Tablet Extract of Bengkuang (Pachyrrhizus erosus) Variation Avicel® Ph 101 and Crospovidone - Rizki Kharisma; Ika Puspita Sari; Angi Nadya Bestari (Majalah Obat Tradisional, 2018)
Bengkuang (Pachyrrhizus erosus) contains daidzein which is pro-estrogenic compound, suppressing bone restoration by directing mechanism in bone estrogen receptor. Bengkuang can be developed into a useful source of phytoestrogens as a supplement in menopausal women. This study aims to determine the stability and influence of Avicel® PH 101 and crospovidone on granular flow properties and physical properties of Bengkuang tuber extract. Bengkuang tuber extracts were made into tablet preparations by wet granulation method. Variation of crospovidone composition was between 2-5%, while Avicel® PH 101 was between 38.86 to 41.86%. The tablet formulation is optimized using the Simplex Lattice Design method. The results show that the addition of Avicel® PH 101 can improve the index of determination, water absorption, moisture content, hardness, time of disintegration, and friability of the tablet, as well as crospovidone addition. Avicel® PH 101 and crospovidone interactions increase water content, decrease hardness, and tablet friability. The optimum tablet formula consists of composition of 293 mg of Avicel® PH 101 and 14 mg of crospovidone per tablet. Testing of optimum formula results with SLD method did not differ significantly to the response of the compression index, hardness and friability of the tablet. The tablet was stable at room temperature (30ºC ± 2 ºC) for four weeks.